IMPROVEMENT OF POWER TRANSFORMERS TESTING EFFICIENCY IN OPERATION CONDITIONS - Lagutin, Valeriy; Teptia, Vira (Scientific Works of Vinnytsia National Technical University, 2015)
The paper considers the device, based on the usage of analog liquid crystal indicator. It enables to define transformation ratio, simultaneously reducing time for measurement, enhances labor productivity of the staff, that performs tests of the transformers. REFERENCES 1. Испытание мощных трансформаторов и реакторов / [Алексеенко Г. В., Ашрятов А. К., Веремей Е. В. и др.] – М.: Энергия, 1978. – 519 с. 2. Справочник по наладке электрооборудования электростанций и подстанций: [под ред. Э. С. Мусаэляна]. – М.: Энергоатомиздат, 1984. – 344 с.